A New One Boat Mid Water Trawl for Indian Waters - Mhalathkar, H. N.; Ramarao, S. V. S.; Mathai, P. George (Fishery Technology, 1975)
Eventhough the rich and variegated pelagic fishery resources of our West-coast is well known much has to be done for a judicial and systematic exploitation on a commercial scale . To fill up this lacuna the present paper describes in detail a new design of 10 .5 m four-equal panel mid-water trawl, its rigging and operation from a medium size vessel . Comprehensive comparative efficiency studies of this gear with a 10 .5m. unequal panel mid-water trawl established the superiority of the new gear . From the results based on the mouth opening, resistance and the catch it is opined that this new gear can not only be used on a commercial scale in harvesting the seasonal pelagic fishery, but also as a secondary supporting gear in shrimp fishery in places like Veraval, where there is a commercially exploitable yield of quality fishes like hilsa, pomfret, seer  etc., without much modification from conventional stern trawlers .